PENGARUH BURNOUT DAN KONFLIK KERJA TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI PADA PERAWAT RSUD DR MOEWARDI SURAKARTA - Valentina, Jesslyn; Suseno, Y. Djoko; Widajanti, Erni (Universitas Slamet Riyadi, 2020)
This study aims to determine the significant influence between: (1) burnout on performance, (2) work conflict on performance, (3) motivation on performance, (4) burnout on performance that is moderated by work motivation, and (5) work conflict on performance which is moderated by motivation in nurses at RSUD Dr. Moewardi Surakarta.The results showed that burnout, work conflict, and motivation significantly influence the performance of nurses Dr. Moewardi Surakarta. In addition, motivation also moderates the effect of burnout and work conflict on the performance of nurses at RSUD Dr. Moewardi Surakarta.